Diagnosis Accuracy of Lung Ultrasound for ARF in Critically Ill Patients: A Systematic Review and Meta-Analysis - Yuan, Xueyan; Liu, Ling; Chang, Wei; Wu, Zongsheng; Huang, Lili; Chao, Yali; Lu, Xinxing; Xie, Jianfeng; Yang, Yi; Qiu, Haibo (Frontiers in Medicine, 2021)
Background Acute respiratory failure (ARF) is a commonly distressing condition in critically ill patients. Its early recognition and treatment may improve clinical outcomes. Mounting evidence suggests that lung ultrasound (LUS) could be an alternative to chest X-ray (CXR) or computed tomography (CT) for the diagnosis of ARF in critically ill patients. This meta-analysis aimed to determine whether LUS can be an alternative tool used to investigate the cause of ARF or thoracic pathologies associated with the diagnosis of ARF in critically ill patients. Method A systematic literature search of the PubMed, Web of Science, Embase, and Cochrane Library databases was conducted from inception to March 2020. Two researchers independently screened studies investigating the accuracy of LUS with CXR or CT for adult critically ill patients with ARF. Data with baseline, true positives, false positives, false negatives, and true negatives were extracted. The study quality was assessed using the Quality Assessment of Diagnostic Accuracy Studies-2 tool. The pooled sensitivity and specificity were obtained using a bivariate model. RESULTS Eleven studies, including 1232 patients, were included in the meta-analysis. Most studies were of low quality. LUS had a pooled sensitivity of 92% (95% confidence interval [CI]: 85–96) and a pooled specificity of 98% (95% CI: 94–99). The area under the summary receiver operating characteristic curve was 98% (95% CI: 97–99). The sensitivity and specificity of LUS to identify different pathological types of ARF were investigated. For consolidation (1040 patients), LUS had a sensitivity of 89% and a specificity of 97%. For pleural effusion (279 patients), LUS had a pooled sensitivity of 95% and a specificity of 99%. For acute interstitial syndrome (174 patients), LUS had a pooled sensitivity of 95% and a specificity of 91%. CONCLUSIONS LUS is an adjuvant tool that has moderate sensitivity and specificity for the diagnosis of different pathological types in critically ill patients with ARF.